Spatial bet hedging, thermal trade-offs and glyphosate: crickets integrate multivariate information during oviposition. (March 2022) - Stahlschmidt, Z.R.; Vo, C.
Abstract : Animals are increasingly exposed to thermal and chemical stressors across spatially heterogeneous landscapes, and adaptive reproductive decisions may mitigate the effects of multiple stressors. Yet, the combined effects of temperature and glyphosate (a broad-spectrum herbicide that is potentially the most commonly used pesticide worldwide) on maternal decision making and terrestrial embryos are unknown. Here, we integrate the effects of temperature, glyphosate (alone and in its commercial formulation, Roundup®) and spatial heterogeneity on oviposition (egg-laying) behaviour, which affects the fitness of females and their offspring. We used the variable field cricket, Gryllus lineaticeps, to test several hypotheses explaining oviposition site selection, specifically the roles of embryo survival, offspring phenotype and maternal survival in oviposition decisions. Temperature (but not glyphosate) affected oviposition and offspring success, with higher performance at intermediate temperatures and lower performance at the extremes, and oviposition increased with the availability of oviposition sites, particularly at warmer temperatures. Environmental context influenced support for oviposition site selection hypotheses. For example, spatial bet hedging (putatively related to maternal survival) was temperature sensitive and it modulated support for the 'offspring phenotype' and 'embryo survival' hypotheses. Specifically, an increased availability of oviposition sites prompted females to oviposit at warmer temperatures, thereby favouring offspring phenotype (increased developmental rate) at an expense to embryo survival (reduced hatching success). In summary, the interconnectedness of spatial and thermal heterogeneity (but not a common pesticide) played large roles in decision making that affects transgenerational fitness. Highlights: We tested hypotheses for oviposition (egg laying) site selection in G. lineaticeps. We examined effects of temperature, glyphosate and spatial heterogeneity. More numerous and warmer sites favoured developmental rate, not embryo survival. Temperature influenced spatial bet hedging during egg laying. Regardless of temperature, glyphosate did not affect egg laying or embryos.